ABORSI AKIBAT KEHAMILAN YANG TAK DIINGINKAN (KTD): Kontestasi Antara Pro-Live dan Pro-Choice - Wijayati, Mufliha (Universitas Islam Negeri Raden Intan Lampung, 2015)
ABORTION DUE TO THE UNWANTED PREGNANCY: The Contestation between Pro-Live and Pro-Choice. Abortion is one of the classic issues which are always interested to be debated. The time of the debating of this abortion issue is as old as the human life. The polarization of the differences of the point of view about this topic is the extreme defense of the interests to pregnant woman. The abortion due to the unwanted pregnancy is an issue which is resurfaced. This paper will talk about abortion due to the unwanted pregnancy which is not only solely on a legal perspective, but also in the political sphere, and social culture. The Utilization of diverse perspectives is not expected to lead to the justification unilaterally, given the complexity surrounding the issue of abortion. The issue of legal, educational, political, social, and cultural have been moved to minimize the presence of unwanted pregnancies and reduce the rate of abortion, and further reduce the number of maternal and child mortality in childbirth